Scandinavian Folk Fishing Communities of Isle Royale National Park: An Ethnographic Study of Commercial Fishing - Stoffle, Richard W. (Bureau of Applied Research in Anthropology, University of Arizona, 2000)
A presentation of findings from the ethnographic study of commercial fishing in the Isle Royale National Park. The complete report, which can be found in this collection, is titled 'The Isle Royale Folkefiskerisamfunn: Familier Som Levde Av Fiske: An Ethnohistory of the Scandinavian Folk Fishermen of Isle Royale National Park.'